Temporal Relationship Between Serum Neurofilament Light Chain and Radiologic Disease Activity in Patients With Multiple Sclerosis - Fox, Robert J; Cree, Bruce A C; de Sèze, Jérôme; Gold, Ralf; Hartung, Hans-Peter; Jeffery, Douglas; Kappos, Ludwig; Montalban, Xavier; Weinstock-Guttman, Bianca; Singh, Carol M; Altincatal, Arman; Belviso, Nicholas; et al. (Neurology, 2024)
BACKGROUND AND OBJECTIVES: Serum neurofilament light chain (sNfL) levels correlate with multiple sclerosis (MS) disease activity, but the dynamics of this correlation are unknown. We evaluated the relationship between sNfL levels and radiologic MS disease activity through monthly assessments during the 24-week natalizumab treatment interruption period in RESTORE (NCT01071083). METHODS: In the RESTORE trial, participants with relapsing forms of MS who had received natalizumab for ≥12 months were randomized to either continue or stop natalizumab and followed with MRI and blood draws every 4 weeks to week 28 and again at week 52 The sNfL was measured, and its dynamics were correlated with the development of gadolinium-enhancing (Gd+) lesions. Log-linear trend in sNfL levels were modeled longitudinally using generalized estimating equations with robust variance estimator from baseline to week 28. RESULTS: Of 175 patients enrolled in RESTORE, 166 had serum samples for analysis. Participants with Gd+ lesions were younger (37.7 vs 43.1, p = 0.001) and had lower Expanded Disability Status Scale scores at baseline (2.7 vs 3.4, p = 0.017) than participants without Gd+ lesions. sNfL levels increased in participants with Gd+ lesions (n = 65) compared with those without (n = 101, mean change from baseline to maximum sNfL value, 12.1 vs 3.2 pg/mL, respectively; p = 0.003). As the number of Gd+ lesions increased, peak median sNfL change also increased by 1.4, 3.0, 4.3, and 19.6 pg/mL in the Gd+ lesion groups of 1 (n = 12), 2-3 (n = 18), 4-9 (n = 21), and ≥10 (n = 14) lesions, respectively. However, 46 of 65 (71%) participants with Gd+ lesions did not increase above the 95th percentile threshold of the group without Gd+ lesions. The initial increase of sNfL typically trailed the first observation of Gd+ lesions, and the peak increase in sNfL was a median [interquartile range] of 8 [0, 12] weeks after the first appearance of the Gd+ lesion. DISCUSSION: Although sNfL correlated with the presence of Gd+ lesions, most participants with Gd+ lesions did not have elevations in sNfL levels. These observations have implications for the use and interpretation of sNfL as a biomarker for monitoring MS disease activity in controlled trials and clinical practice.
Keywords: Female; lidé středního věku; biologické markery; roztroušená skleróza; posuzování pracovní neschopnosti; progrese nemoci; Brain; gadolinium; mužské pohlaví; magnetická rezonanční tomografie; Humans; dospělí; Disability Evaluation; časové faktory; Multiple Sclerosis; neurofilamentové proteiny; Gadolinium; lidé; Male; Middle Aged; mozek; Magnetic Resonance Imaging; Time Factors; Multiple Sclerosis, Relapsing-Remitting; imunologické faktory; ženské pohlaví; Disease Progression; Neurofilament Proteins; relabující-remitující roztroušená skleróza; Adult; Natalizumab; Biomarkers; Immunologic Factors; natalizumab